(untitled) (Scientific journal of the Fergana State University, 2023)
The article provides an analysis of the existing designs of grate cleaners for fibrous materials. Presented their main disadvantages. The design scheme and the principle of operation of the developed grate design of the cleaner of fibrous materials are given. The results of the production tests of the recommended grate design are analyzed. The efficiency of the use of grates installed with a fitting gap between the ends of the teeth of the saw blades of the cylinder and the grate, both with metal and plastic grate